Diversity in the distribution of polysaccharide and glycoprotein epitopes in the cell walls of bryophytes new evidence for the multiple evolution of water-conducting cells - Ligrone, Roberto (The New phytologist, 2002)
•   Although histologically much simpler than higher plants, bryophytes display a considerable degree of tissue differentiation, notably in those groups that possess an internal system of specialized water-conducting cells (WCCs). Here, using a battery of monoclonal antibodies, we examined the distribution of cell wall polysaccharide and glycoprotein carbohydrate epitopes in the gametophyte of four hepatics and eight mosses, with special reference to water-conducting cells. •   CCRC-M7, an antibody against an arabinogalactan epitope, gave a highly consistent and generally specific labelling of WCCs; more variable results were obtained with other antibodies. The labelling patterns indicate that bryophytes exhibit cell and tissue complexity with respect to cell wall components on a par with higher plants. •   A remarkable diversity in the immunocytochemical characteristics of WCCs was observed not only when comparing major bryophyte groups but also within the relatively small and well-circumscribed moss order Polytrichales, indicating that the cell wall biochemistry of WCCs may have been finely tuned in response to specific evolutionary pressures. The immunocytochemical data strengthen the notion that the WCCs in Takakia are not homologous with the hydroids of other mosses nor with the WCCs in Haplomitrium and metzgerialean liverworts. •   The presence of several carbohydrate epitopes in hydroid walls runs strongly counter to the notion that their maturation involves hydrolysis of noncellulosic polysaccharides